2020
DOI: 10.1002/nau.24343
|View full text |Cite
|
Sign up to set email alerts
|

The development and validation of instruments to measure dignity‐protective continence care for care‐dependent older people in residential aged care facilities: A study protocol

Abstract: Aims To develop and validate two instruments to measure dignity‐protective continence care for care‐dependent older people in residential aged care facilities: one instrument to be completed by care recipients and another for healthcare professionals. Methods The first phase of the project will involve a review of literature to identify the attributes of “dignity‐protective continence care” for older people, which will be used to design the initial drafts of the instruments. Thereafter the Delphi survey techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The unique factors identified in the Ghanaian context were family members’ involvement in physical care influenced by cultural and religious beliefs, environmental barriers to privacy and dignity and inadequate involvement in decision making. These factors can inform concept elicitation for the development of a culturally specific PROM for measuring dignified nursing care during acute hospitalisation in Ghana since the majority of dignity‐related PROMs in the literature have been validated for patients in long‐term care (Jacelon & Choi, 2014; Oosterveld‐Vlug et al, 2014; Ostaszkiewicz et al, 2020; Periyakoil et al, 2009; Vlug et al, 2011) settings, and no dignity‐specific PROM has been identified that has been developed and validated in low‐ and middle‐income countries such as Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…The unique factors identified in the Ghanaian context were family members’ involvement in physical care influenced by cultural and religious beliefs, environmental barriers to privacy and dignity and inadequate involvement in decision making. These factors can inform concept elicitation for the development of a culturally specific PROM for measuring dignified nursing care during acute hospitalisation in Ghana since the majority of dignity‐related PROMs in the literature have been validated for patients in long‐term care (Jacelon & Choi, 2014; Oosterveld‐Vlug et al, 2014; Ostaszkiewicz et al, 2020; Periyakoil et al, 2009; Vlug et al, 2011) settings, and no dignity‐specific PROM has been identified that has been developed and validated in low‐ and middle‐income countries such as Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all the existing dignity‐related PROMs are self‐rated scales that can be used to elicit patients' views about their dignity and/or satisfaction with dignified care during an episode of hospital admission. In contrast, dignity‐related PROMs have been validated for patients in long‐term care (Oosterveld‐Vlug et al, 2014; Ostaszkiewicz et al, 2020; Vlug et al, 2011), end‐of‐life care (Chochinov et al, 2008; Periyakoil et al, 2009; Vlug et al, 2011) and community settings (Jacelon & Choi, 2014). PROMs designed for long‐term care, or community settings may not be valid for use in acute hospital settings due to differences in geodemographic characteristics between these settings.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review on patient‐reported dignity during acute hospitalization demonstrates few quantitative studies on hospitalized older adults' dignity and paucity of suitable validated dignity‐related PROMs for hospitalized older adults (Fuseini, Ley, et al, 2022), particularly for the Ghanian population. The few existing dignity‐related PROMs were developed and validated for patients in long‐term care (Dong et al, 2021; Oosterveld‐Vlug et al, 2014; Ostaszkiewicz et al, 2020), end‐of‐life care (Chochinov et al, 2008; Periyakoil et al, 2009; Vlug et al, 2011) or for community‐dwelling older adults (Jacelon & Choi, 2014).…”
Section: Introductionmentioning
confidence: 99%